Targeting lactate metabolism to restore immune homeostasis: a precision therapeutic paradigm for rheumatoid arthritis - Zheng, Lin; A, Xinyu; Ma, Shiyu; Xu, Bo; Xiang, Zheng; Cao, Boran; Shen, Jun; Xu, Xirui; Cheng, Yiwei; Ran, Lei; Shi, Qi; Bian, Yanqin; et al. (Frontiers in Immunology, 2025)
The accumulation of lactate in synovial microenvironment of rheumatoid arthritis (RA) patients is closely correlated with disease activity, with elevated lactate levels serving as both biomarkers and pathogenic mediators in RA progression. In recent years, mounting evidence has demonstrated that lactate-driven metabolic reprogramming constitutes the central hub of the immune-metabolic-bone destruction axis in RA. The accumulation of lactate in the synovial microenvironment triggers a cascade of immunoregulatory effects, and these metabolic alterations create a self-perpetuating cycle of inflammation and tissue destruction, which represents the fundamental cause of RA chronicity. Therefore, lactate metabolism has been identified as a therapeutic target, opening new avenues for precision medicine approaches in RA treatment. Novel therapeutic strategies targeting lactate dehydrogenase A (LDHA) inhibitors, monocarboxylate transporters (MCTs), and enzymes that regulate lactylation have shown promising preclinical results. Furthermore, combination therapies pairing metabolic modulators with conventional biologics demonstrate synergistic effects in suppressing inflammatory pathways while improving drug penetration into synovial tissues. Additionally, patient stratification based on lactate metabolic profiles enables personalized treatment approaches. In summary, targeting lactate metabolism represents a paradigm shift in RA treatment from symptom management toward metabolic restoration. The integration of metabolic modulators with existing therapeutic regimens holds promise for achieving sustained remission and preventing long-term joint damage.